2020
DOI: 10.1080/13218719.2020.1739577
|View full text |Cite
|
Sign up to set email alerts
|

Absence of insight as a catch-all extra-legislative factor in Swedish mental health law proceedings

Abstract: Previous research indicates that insight is frequently used but rarely defined in mental health proceedings. This article examines how participants in Swedish administrative court proceedings use the concept of insight when discussing decisions regarding involuntary psychiatric care. Open-ended qualitative interviews were conducted with professional mental health court participants. The results show that lack of insight is used by the informants as an argument for all three legal criteria for involuntary psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, since Sweden's entry into EU, the legal protection of civil rights has been strengthened. In the case of compulsory care, this includes “the right to an oral hearing, the right to a cost-free legal representative and the demand on the court to hear a specialist in psychiatry as an expert witness” (Radovic, Eriksson, and Dahlin 2020: 604). According to contemporary legislation, a compulsory care case is initiated either by the patient who rejects a suggested treatment or by the chief psychiatrist at the hospital seeking legal approval for compulsory care longer than four weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, since Sweden's entry into EU, the legal protection of civil rights has been strengthened. In the case of compulsory care, this includes “the right to an oral hearing, the right to a cost-free legal representative and the demand on the court to hear a specialist in psychiatry as an expert witness” (Radovic, Eriksson, and Dahlin 2020: 604). According to contemporary legislation, a compulsory care case is initiated either by the patient who rejects a suggested treatment or by the chief psychiatrist at the hospital seeking legal approval for compulsory care longer than four weeks.…”
Section: Methodsmentioning
confidence: 99%
“…In compulsory care trials in Sweden, the chief psychiatrist wins these proceedings 99% of the time (Zetterberg et al 2014). The major reason for this is that the court-appointed psychiatrists, who are assigned to provide the court with a second opinion on treatments and diagnosis, and the chief psychiatrists almost always agree on treatment, which makes it difficult for the court to reject the psychiatric diagnosis and suggested treatment (Sjöström et al 2002; Radovic et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This legislation differs from that in most other countries since it does not have a legal insanity defense, but a presumption against sentencing convicted severely mentally disordered offenders to prison. Such offenders are instead held legally accountable for their crimes but are sentenced to forensic psychiatric care, which is a bona fide legal sanction reserved for this specific type of convicted offenders ( 3 ). If it is required that such a person, considering their mental state and personal circumstances, is admitted to a hospital for psychiatric care, the court will transfer this person to such a hospital, where the conditions include deprivation of physical liberty and coercive care interventions ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it has been repeatedly suggested that insight is used as an extralegislative criterion for paternalistic interventions in mental health care (e.g. O'Keefe, 2022;Radovic et al, 2020;Gurbai, Fitton and Wayne, 2020;Guidry-Grimes, 2019;Case, 2016;Feckelton, 2010;Dawson and Mullen, 2009;Diesfield and Stojstrom, 2007). In England, the Independent Review of the Mental Health Act 1983Act (2018) concluded that people's experiences, knowledge and reasoning are overlooked by mental health professionals and 'mislabelled as lack of insight or aspect of their disorder', while the study conducted by Owen et al (2009) found that lack of insight is the most significant predictor of incapacity in psychiatric care.…”
Section: Introductionmentioning
confidence: 99%